Synthesis and in Vitro Evaluation of 9-Anilino-3,6-diaminoacridines Active Against a Multidrug-Resistant Strain of the Malaria Parasite Plasmodium falciparum - Swarna A. Gamage (2018)
A series of 9-anilinoacridines have been prepared and evaluated for their activity against a multidrug-resistant K1 strain of the malaria parasite Plasmodium falciparum in erythrocyte suspensions. 3,6-Diamino substitution on the acridine ring resulted in lower mammalian cell cytotoxicity and higher antiparasitic activity than other substitution patterns, providing compounds with the highest in vitro therapeutic indices. A new synthesis of 3,6-diamino-9-anilinoacridines, via reduction of the corresponding diazides, gives much higher yields than traditional methods. Within the subset of 3,6-diamino-9-anilinoacridines, there was considerable tolerance to substitution at the 1′-anilino position. In a sharp divergence with structure-activity relationships for high mammalian cell toxicity and anticancer effects, derivatives bearing electron-withdrawing 1′-substituents (e.g., SO 2 - NHR and CONHR) showed the most potent antimalarial activity (IC 50 values of 10–20 nM). Representative compounds were shown to be potent inhibitors of the DNA strand-passing activity of human topoisomerase II and of the DNA decatenation activity of the corresponding parasite enzyme. The 1′-SO 2 NH 2 derivative 7n completely inhibited strand passage by Jurkat topoisomerase II at 20 μM, and an increase in linear DNA (indicative of inhibition of religation) was seen at or above 1 μM. It also inhibited the decatenating activity of the parasite topoisomerase II at 6 μM and above. In contrast, the analogous compound without the 3,6-diamino substituent was inactive in both assays up to 100 μM. Overall, there was a positive relationship between the ability of the drugs to inhibit parasite growth in culture and their ability to inhibit parasite topoisomerase II activity in an isolated enzyme assay. The 1′-SO 2 NH 2 derivative 7n showed a high IVTI (1000) and was a potent inhibitor of both P. falciparum in vitro (IC 50 20 nM) and P. falciparum-derived topoisomerase II. However, the compound was inactive against Plasmodium berghei in mice; reasons may include rapid metabolic inactivation (possibly by N-acetylation) and/or poor distribution. © 1994, American Chemical Society. All rights reserved.